FABRIKASI NANOTUBES TiO2 DENGAN TINGKAT NANOKRISTALINITAS TINGGI MELALUI PERLAKUAN KOMBINASI ANIL DAN PASCA-HIDROTERMAL UNTUK APLIKASI SEL SURYA TERSENSITISASI ZAT PEWARNA[Fabrication of Highly Nanocrystalline TiO2 Nanotubes Through a Combination of Pre-Annealing and Hydrothermal Treatment for Dye Sensitized Solar Cell Application] - Ferdiansyah, Alfian; Yuwono, Akhmad Herman; Sofyan, Nofrijon; Kartini, Indriana; Pujianto, Tego Hadi; Munir, Badrul (Jurnal Metalurgi, 2012)
In the recent years TiO2 nanotube structure has attracted a great attention due to its very high surface area to volume ratio. This property plays an important role on the dye sensitized solar cell electrodes applications. In this study, TiO2 nanotubes have been fabricated through hydrothermal technique by dissolving Degussa P25 TiO2 nanopowder in a highly concentrated alkaline solution of sodium hydroxide into a sealed autoclave. In order to improve nanocrystallinty of TiO2 nanotubes structure, a modification was made by combining conventional annealing process and hydrothermal post. Details of the structure, morphology and crystallinity of products were analized by XRD, Raman spectroscopy, SEM and TEM, while the optical properties of the nanotubes was examined by UV-Vis spectroscopy. The investigation result showed that enhancing nanocrystallinity while at the same time maintaining the integrity of the nanotube hollow structure can be obtained by the combined process of conventional annealing and post-hydrothermal treatment. For the nanotube samples which have been previously annealed at 150 °C, the crystallite size of anatase TiO2 increased from 6.93 to 7.82 nm after post-hydrothermal treatment of 80-150 °C. A more significant enhancement in the 142 | Majalah Metalurgi, V 27.2.2012, ISSN 0216-3188/ hal 141-150 nanocrystallinity can be achieved when the annealing temperature was raised to 300 ° C, followed by posthydrothermal. This resulted in the crystallite size of anatase TiO2 nanotubes increased from 17.20 to 18.30 nm. The band gap energy of resulting nanotubes is inversely proportional to crystallites size, where the lowest value of 3.19 eV obtained from the largest crystallite size is 18.30. In the DSSC fabrication device, this nanotubes also shown the highest open-circuit voltage of 108 mV.